Three cocluded insect viruses : a biophysical and biological study of the nuclear-polyhedrosis virus of Colias electo, the granulosis virus of Heliothis armigera and the nuclear-polyhedrosis virus of Heliothis zea - Gitay, Hela (Division of Medical Microbiology, 2017)
An investigation was undertaken in some detail of three virus strains of insect pests of agricultural importance, viz. a nuclear-polyhedrosis virus of the lucerne caterpillar, Colias electo, and a granulosis virus of the bollworm, Heliothis armigera, both found in South Africa, and a nuclear-polyhedrosis virus of the bollworm, Heliothis zea, isolated in America, with a view to ascertaining a knowledge of some of the fundamental properties and basic biology of these infective agents. On the basis of the information gained the viruses could be differentiated and their broad classification was established. The morphology of the polyhedra, capsules and virus particles observed by light and electron microscopy has been completed and measurements of the viral elements have been made. Some biophysical properties of the virus particles and their inclusion bodies were recorded, i.e. their resistance to chemical and physical treatments and their relative mobility in an electric field under standard conditions. Observations were made on procedures which brought about varying degrees of purification and concentration of the virus particles from putrefying larvae and the most successful of these were found to be reproducible. They involved the purification of the inclusion bodies and their digestion by weak alkali to release the virus particles. Both preparations of the viral elements were further purified by zone electrophoresis in sucrose density gradients. Some information was gathered on the mode of transmission of the infection from insect to insect by contact or cannibalism, from one generation to the next through the eggs, and particularly from one area to another by virus survival in avian faeces. The incidence and rate of the infection in the larvae was increased by environmental changes such as raising the temperature and also to some extent by spraying with a suspension of endospores of Bacillus thuringiensis. Exposure to other stress conditions was not successful in initiating a fatal infection in the insects. Of particular interest, however, was the observation that by injecting a 'foreign' virus a fatal infection was induced by activation of a native occult virus in the larvae of the silkworm, Bornbyx mori. In the context of the possible application of these infective agents to future methods of biological control of economically disastrous pests, these preliminary experiments were not unrewarding.